PENGARUH STRATEGI PEMBELAJARAN RAFT (ROLE–AUDIENCE–FORMAT–TOPIC) TERHADAP KEMAMPUAN MENULIS TEKS TANGGAPAN SISWA KELAS VII UPT SMP NEGERI 27 MEDAN - Ganda Munthe, Ilham; Prihasti Wuriyani, Elly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the RAFT (Role–Audience–Format–Topic) learning strategy on the ability to write response texts for grade VII students of UPT SMP Negeri 27 Medan. The main problem in this study is the low ability of students to structure response texts as a whole, analyze linguistic elements, and express ideas logically due to the dominance of conventional strategies. This quantitative study used an experimental method with a two-group post-test only design. The research sample consisted of 62 students selected through random sampling techniques, then divided into an experimental class (VII-9, n = 31) with the RAFT strategy and a control class (VII-7, n = 31) with an expository strategy. Data were collected through a written test of writing response texts, then analyzed using the Lilliefors normality test, Fisher's homogeneity test, and the independent sample t-test. The results showed that the average score of the experimental class (76.13) was higher than that of the control class (72.42). Based on the t-test results, the calculated t value = 5.54 was obtained, which was greater than the t table = 2.00 at a significance level of α = 0.05. Thus, H0 was rejected and Ha was accepted. It can be concluded that the RAFT learning strategy has a significant effect on improving students' ability to write response texts.